EPIZOOTOLOGICAL FEATURES OF STRONGYLOIDIASIS OF SHEEP IN THE CONDITIONS OF POLTAVA REGION - Sorokova, S. S. (Scientific Progress & Innovations, 2022)
Strongyloidiasis is a fairly common disease among both domestic animals and wildlife. Among ruminants, in particular sheep, the disease is caused by the nematode Strongyloides papillosus (Wedl, 1856), which causes significant damage to animals, ranging from trivial disorders of the digestive system to the death of animals at high intensities of invasion. The causative agent of the disease is extremely common in many countries around the world and is adapted to exist in different climatic zones, which contributes to the complex biology of the parasite. The aim of the study was to determine the epizootiological features of strongyloidiasis infestation of sheep in the conditions of farms in Poltava region. To achieve this goal, a study of 2108 heads of sheep of 4 age groups – lambs up to 4 months, young 4–12 months, sheep 12–24 months, sheep older than 24 months, kept in sheep farms of various forms of ownership and capacity on the territory of Poltava, Myrhorod, Kremenchug and Lubny districts of Poltava region. Coprooscopic studies of sheep were carried out in the laboratory of parasitology of the Department of Parasitology and Veterinary Sanitary Examination of Poltava State Agrarian University by the quantitative method of Trach. It was found that strongyloidiasis of sheep is a common infestation in the Poltava region with an average prevalence of 30.88 % and intensity of invasion of 280.07±14.20 eggs in 1 g of feces. Poltava district was the most unfavorable for the disease, where the highest rates of both extensiveness and intensity of invasion were recorded (57.17 % and 324.52±15.60 eggs in 1 g of feces, respectively). It is proved that in the territory of Poltava region strongyloidiasis is more often registered among young animals aged 4–12 months of age where the prevalence index averaged – 50.07 %, for intensity of invasion – 391.21±20.72 eggs in 1 g of feces. Studies show that most often strongyloidiasis in sheep in the Poltava region is part of mixed invasions, which account for 79.88% of the total number of sick animals. A total of 14 species of mixed invasions were identified, among which causative agents of digestive tract nematodes (strongylidosis of the digestive tract, nematodyrosis, trichurosis), cestodes (moniesiosis) and protozoa (eimerosis) in various combinations were identified. Among mixed invasions, two-, three-, four-, and five-component associations were recorded (79.04, 13.27, 4.81, and 2.88 %, respectively, of the total number of patients in mixed invasions).